Consumers’ attitudes toward consumerism, perceptions of specific product-related variables and consumer complaint intention : a Lesotho perspective - Donoghue, Sune (University of Pretoria, 2017)
Dissertation (MConsumer Science)--University of Pretoria, 2017.